Spatio-temporal long-term evaluations of the mean sea level pressure, sea level change, and sea surface temperature over two enclosed seas - Islek, Fulya; Yuksel, Yalcin (ELSEVIER, 2023)
This study aims to examine the temporal and spatial variability of mean sea level pressure (MSLP) and to determine the relationship between MSLP and the oceanic data, such as sea surface temperature (SST), and sea level anomaly (SLA). The long-term and decadal averages, long-term trends, and their statistical significance levels were evaluated in the eastern Mediterranean and Black seas as enclosed sea examples. In the Black Sea, the western part was exposed to higher MSLP accompanied by relatively low sea level rise compared to the eastern part of the sea. In the eastern Black Sea, significant sea level rise was detected, where the MSLP was low due to the inverse barometer (IB) effect. In the eastern Mediterranean Sea, MSLP was significantly decreased eastward and was accompanied by relatively high sea level rise compared to other parts of the basin. The highest MSLP was found in the Aegean Sea, where the sea level rise was relatively low. In recent years, significant warming tendency in SST triggers a significant decreasing trend in MSLP and the rising tendency in sea level over the eastern Mediterranean and Black seas. & COPY; 2023 Elsevier B.V. All rights reserved.
Keywords: Sea level pressure; Sea surface temperature; Sea level; Black Sea; Mediterranean Sea; BLACK-SEA; INTERANNUAL VARIABILITY; NORTH-ATLANTIC; TRENDS; WIND; OSCILLATION; ANOMALIES; ALTIMETRY; CLIMATE; Environmental Sciences & Ecology; Marine & Freshwater Biology